2016
DOI: 10.1126/science.aaf8287
|View full text |Cite
|
Sign up to set email alerts
|

Basidiomycete yeasts in the cortex of ascomycete macrolichens

Abstract: For over 140 years, lichens have been regarded as a symbiosis between a single fungus, usually an ascomycete, and a photosynthesizing partner. Other fungi have long been known to occur as occasional parasites or endophytes, but the one lichen-one fungus paradigm has seldom been questioned. Here we show that many common lichens are composed of the known ascomycete, the photosynthesizing partner, and, unexpectedly, specific basidiomycete yeasts. These yeasts are embedded in the cortex, and their abundance correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
351
3
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(366 citation statements)
references
References 65 publications
5
351
3
7
Order By: Relevance
“…Researchers have evaluated the distribution of contaminants in relation to wind patterns in large population centers like Los Angeles as well as industrial areas [3,37]. Studies have shown that metal contamination from anthropogenic sources originate from PM2.5 and PM10 atmospheric input [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have evaluated the distribution of contaminants in relation to wind patterns in large population centers like Los Angeles as well as industrial areas [3,37]. Studies have shown that metal contamination from anthropogenic sources originate from PM2.5 and PM10 atmospheric input [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mycobiont in most lichens is an ascomycete, a recent study shows that a basidiomycete yeast is invariably involved in this mutualism as a third partner (Spribille et al 2016). Additionally, lichens are associated with fungi lichenicolous fungi, endolichenic fungi and culturable and non-culturable non-photosynthetic bacteria (Biosca et al 2016; Muggia et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lichens are a fungal growth form, consisting of a symbiotic partnership between a fungus and a photosynthetic organism, either a eukaryotic alga (in the green algal family Trebouxiaceae) or a cyanobacterium and sometimes both (Purvis and Pawlik-Skowronska 2008). It is now known that they can also contain a yeast as another fungal partner (Spribille et al 2016). Lichens are pioneer colonisers of rocks, and initiators of bioweathering biofilms that are involved in the early stages of mineral soil formation.…”
Section: Characteristics Of Rock Transforming Fungimentioning
confidence: 99%